2002
DOI: 10.1080/00365510260296483
|View full text |Cite
|
Sign up to set email alerts
|

Serum matrix metalloproteinase-9 concentration in angiographically assessed coronary artery disease

Abstract: Expression of several matrix metalloproteinases (MMPs) in atherosclerotic plaques has been well documented, and there are findings to indicate that arterial inflammation is reflected in increased serum concentration of matrix metalloproteinase-9 (MMP-9). In coronary atherosclerosis, there is enhanced expression of this MMP, which may be predictive of the severity of the disease. We determined the concentrations of serum MMP-9 in 61 patients (47 males, 14 females) who had >50% obstruction in one or more coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 29 publications
7
48
1
4
Order By: Relevance
“…Our results support the recent findings suggesting that genetic variations in humans that effect MMP-9 expression influence the development and progression of atherosclerosis 8 and that elevated levels of MMP-9 in serum are seen in patients with severe coronary stenosis. 9,37 We further showed that the resident cells and not the bone marrow-derived cells were indeed the source of MMP-9 affecting the plaque composition in this model of injury-induced accelerated atherogenesis. As stated previously, we used a mixed background (50% C57BL/6 and 50% 129 SvEv) for this rapid atherogenesis.…”
Section: Discussionmentioning
confidence: 74%
“…Our results support the recent findings suggesting that genetic variations in humans that effect MMP-9 expression influence the development and progression of atherosclerosis 8 and that elevated levels of MMP-9 in serum are seen in patients with severe coronary stenosis. 9,37 We further showed that the resident cells and not the bone marrow-derived cells were indeed the source of MMP-9 affecting the plaque composition in this model of injury-induced accelerated atherogenesis. As stated previously, we used a mixed background (50% C57BL/6 and 50% 129 SvEv) for this rapid atherogenesis.…”
Section: Discussionmentioning
confidence: 74%
“…Although circulating MMP-9 levels may be elevated in patients with HF 11,22 and in patients with coronary disease, 24,25 our data suggest that plasma MMP-9 is unlikely to be an informative biomarker in a low-risk sample of the general population.…”
Section: Clinical Correlates Of Detectable Plasma Mmp-9mentioning
confidence: 72%
“…Previous investigations have been conducted in small samples of highly selected individuals. Some studies have reported that plasma MMP-9 levels are higher in patients with coronary disease, 24,25 diabetes, 26 and dyslipidemia 25 and in smokers. 27 Others have reported lower serum MMP-9 levels in hypertensive individuals.…”
mentioning
confidence: 99%
“…Regarding the role in atherosclerotic plaque, previous studies (37,38) have demonstrated that the plasma MMP-9 level in patients with coronary artery disease correlated to the severity of coronary atherosclerotic plaques and the presence of plaque rupture in the culprit lesion. The prognostic role of MMP-9 was also demonstrated by Blankenberg et al (39), who demonstrated that the MMP-9 level could be used as a predictor for cardiovascular mortality in patients with coronary artery disease (24).…”
Section: Mmps As a Prognostic Indicatormentioning
confidence: 99%